FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI GREEN FINANCE PADA PERBANKAN DI INDONESIA - Risna Kartika; Andini Grace Tinia; Toto (Universitas Islam Balitar, 2025)
This research aims to analyze the factors influencing the adoption of green finance in the Indonesian banking sector. Green finance serves as an important strategy to support sustainable development through environmentally friendly financing activities. The research uses a literature review method by examining various national and international journal articles, official reports from the Financial Services Authority (OJK), and publications from global financial institutions related to green finance policies and practices. The results indicate that the main factors affecting the adoption of green finance are government regulations and OJK’s sustainable finance policies. Internal factors such as environmental awareness, top management support, technological innovation, and market pressure also play a significant role in accelerating implementation. However, the adoption of green finance in Indonesia remains relatively low and is still largely administrative, rather than being integrated into long-term business strategies. The study also identifies a research gap in examining the relationship between green finance and bank performance. Therefore, this study is expected to serve as a foundation for developing future policies and research to strengthen the implementation of green finance in Indonesia.